Influence of Non-Genetic Factors on Milk Yield and Composition in Jersey and Holstein-Friesian Crossbred Cows in a Commercial Cattle Farm of Chitwan, Nepal - Sharma, Surya Prasad; Gyawali, Amita (Journal of Agriculture and Forestry University, 2026)
The study was carried out to find out the effect of non-genetic factors on milk yield and milk composition traits of Jersey and Holstein Friesian (HF) crossbred on farm from 2021 to 2023 at Shree Laligurans Dairy Farm and Research Center, Chitwan district of Nepal. Altogether, 2030 daily milk records of 400 lactating crossbred cows (HFX-271, JX- 129) maintained under uniform management were analyzed. Breed, parity, stage of lactation, season of milking, and month of calving were considered as non-genetic factors affecting average daily milk yield and milk composition traits (fat, SNF, and protein) significantly. The least square analysis was performed by using Harvey (1990) software package, and comparison of significant means was done by using Duncan’s Multiple Range Test (DMRT). The least square mean and standard error for daily milk yield of Holstein and Jersey crossbred cows in the study were 9.65±0.92 and 9.54±1.20 liters, respectively. The result revealed the non-significant effect of breed on milk yield and fat%, but a significant effect on other milk composition traits such as SNF% and protein%. The overall means for fat, SNF, and protein were 4.56%, 8.68%, and 3.09%, respectively. Furthermore, stage of lactation, season of milking, and month of calving significantly affected both milk yield and composition. Based on these findings, Jersey crossbred cows are better suited for milk yield and composition quality within the sub-tropical agro-climatic conditions of Chitwan. To optimize commercial dairy productivity, it is recommended to synchronize calving and milking schedules with the spring season and keep the best milk-producing cows on the farm for three to six milking cycles (parity) before culling them.